A compact f-f model of high-dimensional piecewise-linear function over a degenerate intersection - Chengtao Wen; Shuning Wang; Feng Li; Khan, M.J. (IEEE transactions on circuits and systems. I, Regular papers, 2005)
A novel f-f model is developed constructively which can express any n-dimensional piecewise linear (PWL) function by a superposition of basis functions if it is defined over an nth-order degenerate intersection formed by (n-1)th-order minimal degenerate intersections. We also propose the concrete functional forms of nth-order basis functions. Being the simplest type of the minimal degenerate intersection, the basis function is the most elementary "building block" of a PWL function defined in an arbitrary-dimensional space. In addition, the model constitutes a natural continuation to Julian's canonical formulation and can bridge the lattice PWL model and the well-established canonical representation.